Sam's letters to Jennifer : a novel - Patterson, James, 1947- (New York : Grand Central, 2006)
Jennifer returns to the resort village where she grew up and two letters change her life; she discovers she still has the capability to fall in love.
Booklist
Adult.
Adult
Keywords: Letters -- Fiction; Man-woman relationships -- Fiction; Letters -- Fiction; Love stories; Man-woman relationship -- Fiction; Love stories